Energy storage system for increasing electric-power stability - Acosta, Jorge Javier Sánchez; Gámez, María Rodríguez; Alaba, Lenin Agustín Cuenca; Arauz, Wilber Manuel Saltos; Alvarez, José Ricardo Nuñez; Pérez, Antonio Vázquez (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
At present, energy storage systems are being generalized due to the necessity of providing stable and good-quality electrical service in all homes. Solutions are given to Ecuador's electrical power system using distributed generation facilities with different renewable energy sources. However, some of those facilities in the Province of Manabí are located relatively far from the power consumption areas, causing an energy deficit in some electrical feeders when demand increases. The objective of the present study is to analyze the functioning of an electrical feeder when energy storage systems and photovoltaic systems are connected as a hybrid system. Two different software, CYME, and ArcGIS, were used to analyze the electrical power system in the province object of study and to design the simulation that showed better functioning of the electrical feeder when energy storage systems are connected than with connection to photovoltaic systems.